HIGH-DENSITY CONCRETE AS A RADIATION SHIELDING – SYSTEMATIC LITERATURE REVIEW - Ranna, Prima; Fuk Jin, Oei (Jurnal Infrastruktur, 2024)
High-density concrete (HDC) has been extensively employed as radiation shielding owing to its high density and capacity to absorb gamma rays and neutrons. The optimal average density of HDC for protecting against various types of radiation generally ranges from 2.2 g/cm³ to 3.5 g/cm³. This density may vary depending on the type of aggregate used, such as serpentine, barite, siderite, magnesite, and others. The study analyzes the use of high density concrete as a radiation protector using systematic literature review. The research method uses the PRISMA methodology with data search using the Publish or Perish (PoP) application with the keywords "High-Density Concrete," "Materials," and "Radiation Shielding" on the Scopus database. Bibliometric analysis using VOSviewer visualizes relationships between key terms in research. The results show that the average optimal density on high density concrete for radiation protectors varies, depending on the type of aggregate used.The selection of aggregates has a significant impact on the performance of concrete in radiation protectors. Aggregates such as barite, hematite, magnetite, and industrial waste (such as CRT glass and EAF barrel) are effective in enhancing radiation protection performance. Overall, the compressive strength of high-density concrete is an important factor in ensuring structural stability and effectiveness as a radiation shield. This study provides an in-depth perspective on the development of high-density concrete as radiation shielding and offers directions for future research in this field.